Cohort Study Examining the Association Between Blood Pressure and Cardiovascular Events in Patients With Peripheral Artery Disease. Issue 6 (19th March 2019) - Thomas Manapurathe, Diana; Moxon, Joseph Vaughan; Krishna, Smriti Murali; Rowbotham, Sophie; Quigley, Frank; Jenkins, Jason; Bourke, Michael; Bourke, Bernard; Jones, Rhondda E.; Golledge, Jonathan
Abstract : Background: Hypertension is an important risk factor for cardiovascular events in patients with peripheral artery disease; however, optimal blood pressure targets for these patients are poorly defined. This study investigated the association between systolic blood pressure (SBP) and cardiovascular events in a prospectively recruited patient cohort with peripheral artery disease. Methods and Results: A total of 2773 patients were included and were grouped according to SBP at recruitment (≤120 mm Hg, n=604; 121–140 mm Hg, n=1065; and >140 mm Hg, n=1104). Adjusted Cox proportional hazards analyses suggested that patients with SBP ≤120 mm Hg were at greater risk of having a major cardiovascular event (myocardial infarction, stroke, or cardiovascular death) than patients with SBP of 121–140 mm Hg (adjusted hazard ratio, 1.36; 95% CI, 1.08–1.72; P =0.009). Patients with SBP >140 mm Hg had an adjusted hazard ratio of 1.23 (95% CI, 1.00–1.51; P =0.051) of major cardiovascular events compared with patients with SBP of 121–140 mm Hg. These findings were similar in sensitivity analyses only including patients receiving antihypertensive medications or focused on patients with a minimum of 3 months of follow‐up. Conclusions: This cohort study suggests that patients with peripheral artery disease and SBP ≤120 mm Hg are at increased risk of major cardiovascular events. The findings suggest caution in intensive SBP lowering in this patient group.